ANALISIS PERFORMANSI ALAT OTOMASI PENYARINGAN AIR SISA PENCUCIAN SURIMI: STUDI KASUS - Hollanda Arief Kusuma; Unai Sunardi; Sapta Nugraha; Dwi Eny Djoko Setyono (TEKTRIKA, 2022)
The aim of this research is to develop an automated instrument for filtering surimi washing wastewater. The tool consists of a water suction system, a filtration system using a plankton net, and temperature sensors DS18B20 and distance sensors JSN-SRT04. The results show that the automated surimi washing wastewater filtering instrument has been successfully developed and can produce 343 grams and 199 grams of filtered meat from 1 kg of meat in two trials. The water turbidity data before and after the filtration process also shows that the instrument can reduce turbidity by 88% allowing the surimi washing wastewater to be reused. This demonstrates that waste reduction can be applied to this instrument. Data from DS18B20 temperature sensor and JSN-SRT04 distance sensor also show accurate and precise data patterns. DS18B20 calibration shows average error by 2.51%, RMSE by 1.47 ?C, and standard deviation by 0,7 ?C. JSN-SRT04 calibration shows average error by 3.07%, RMSE by 1.99 cm, and standard deviation by 0.45 cm. Therefore, the automated surimi washing wastewater filtering instrument is an effective solution for utilizing surimi washing wastewater and reducing liquid waste. The implementation of this tool would be very beneficial to the surimi processing industry in reducing waste and preserving the environment. This instrument can also be used as a reference for developing other automated instruments in the field of wastewater treatment. Key Words: Surimi, zero waste, acoustic sensor, temperature sensor